Comparison of Three Dimensional Partially and Fully Depleted SOI MOSFET Characteristics Using Mathcad - Neha Goel; Manoj Kumar Pandey (Журнал нано- та електронної фізики)
In this Paper, comparison of three Dimensional characteristics between partially and fully depleted Silicon-On-Insulator (SOI MOSFET) is presented, this is done through 3D device modeling using mathcad, based on the numerical solution of three dimensional Poisson’s equation. Behavior of Various Parameters like Surface Potential, Threshold Voltage, Electric field and Drain current are presented in this paper.